Comparative evaluation of orthodontic mini-implants hygiene protocols on subgingival bacterial load - Amanda Osório Ayres de FREITAS; Ana Paula Vieira COLOMBO; Celuta Sales ALVIANO; Daniela Sales ALVIANO; Renata Martins do SOUTO; Deborah Catharine de Assis LEITE; Isabela Lopes Vale Pedrosa LIMA; Matilde da Cunha Gonçalves NOJIMA (Dental Press Journal of Orthodontics)
ABSTRACT Objective: The aim of this study was to evaluate the effectiveness of four hygiene protocols for orthodontic mini-implants in reducing the subgingival bacterial load in the peri-implant sulcus. Methods: Thirty-nine healthy individuals who had fifty-nine as-received mini-implants (20 men, 19 women, 20 to 42 years old) were randomly distributed into four groups of hygiene protocols: mechanical hygiene (M); mechanical hygiene associated with 0.12% digluconate chlorhexidine (CHX), 0.03% triclosan (T), or 0.05% cetylpyridinium chloride (CP). All individuals were instructed regarding the hygiene procedures (T0). For bacterial load analysis, the gingival crevicular fluid from peri-implant sulcus was collected and submitted to quantitative real-time PCR at baseline (T1) and after 21 days following the hygiene protocols (T2). Wilcoxon test was applied for intergroup comparisons, whereas differences among groups at each time point were examined by Kruskal-Wallis test. The significance level was 5%. Results: Significant difference was detected between baseline and post-protocol times for bacterial total counts, comparing intergroup results, except for mechanical hygiene associated with cetylpyridinium chloride (M p=0.018, CHX p=0.028, T p=0.012, CP p=0.065). No significant difference was detected among the evaluated methods (p=0.181). Conclusions: The mechanical hygiene of orthodontic mini-implants itself was capable to reduce total bacteria load and keep devices clean. Commonly, orthodontists prescribe, in addition to mechanical biofilm removal, some protocols combining adjunctive chemical agents as chlorhexidine. The authors believe that results have large importance for dental community, as they can protect patients from overtreatment.